Transformative Adab Pedagogy Based on the Thought of Az-Zarnuzi, Al-Ghazali, and Abdullah Al-Haddad and Its Relevance to Phase A Adab Education Program in Elementary Schools - Nanih Suhernih; Santi Lisnawati; Nesia Andriana; Wido Supraha; Ahmad Sastra (Al-Ulum: Jurnal Pendidikan Islam, 2026)
This study aims to formulate the concept of transformative adab pedagogy, a learning model that integrates the personal, spiritual, and social adab values of the three scholars within the context of the Phase A Adab Education program (grades 1–2 of elementary school). This study employs a library research method. The results of the analysis indicate that Az-Zarnuji's ideas regarding the discipline (adab) of learning, Al-Ghazali's concepts of purification of the soul (tazkiyatun nafs) and intention, and Al-Haddad's emphasis on the consistency of worship and social ethics can be collaborated into a comprehensive framework. The implementation of this pedagogy focuses on habituation, exemplary conduct (role modeling), value internalization, and socio-emotional engagement between teachers and students. In conclusion, the synthesis of the thoughts of these three scholars produces a transformative adab pedagogical model that is operational for application in early-phase learning. This model not only strengthens the cultivation of spiritual foundations and self-discipline from an early age but also offers a practical solution to the challenges of educational secularism in Indonesian elementary schools.